THE INFLUENCE OF HUMAN LEUKEMIA DIFFERENTIATION FACTOR ON ABILITY OF BLOOD CELLS TO PRODUCE IL-1β, IL-1ra AND IL-8 IN CHRONIC ATROPHIC GASTRITIS, ADENOMAS AND ADENOCARCINOMAS OF THE STOMACH - A. V. Sosnina (SPb RAACI, 2015)
We studied biological effects of Human Leukemia Differentiation Factor (HLDF), first derived from the cultural media of human myelogenous HL-60 leukemia cells, on the production of IL-1β, IL-1ra and IL-8 by immune cells from the patients with chronic atrophic gastritis, adenomas and adenocarcinomas of the stomach. To evaluate the influence of HLDF on cytokine-producing function of the whole blood cells, the latter were incubated with this factor or without it. The levels of IL-1β, IL-1ra and IL-8 were determined in supernates of these cells. The stimulation indices of HLDF upon cytokine production were estimated as a cytokine production ratio of stimulated versus resting cells. Histological analysis of gastric mucous tissue samples and removed tumors was also performed. It was revealed that, in chronic atrophic gastritis, HLDF significantly increased IL-1ra and IL-8production. In patients with stomach adenomas and adenocarcinomas, HLDF increased IL-1ra, IL-8 and IL-1β production. In cases of stomach adenomas, the indices of HLDF stimulation upon blood cells cytokine production are significant higher than in patients with chronic atrophic gastritis. Interdependence study between the stimulation indices of HLDF and histological parameters of gastric mucosa and tumor samples have shown a negative correlations between the stimulation index of HLDF upon IL-1ra production and the grade of intestinal metaplasia and dysplasia of the adenoma epithelium, and a positive correlation between the stimulation index of HLDF on IL-8 production and the intensity of lymphoid infiltration of the adenomas. In patients with gastric adenocarcinomas, a positive correlation between the stimulation index of HLDF on IL-8 production and number of blood vessels with tumor embolus was revealed. One may presume that immune cells activation caused by HLDF may exert following actions: (1) triggering some processes of chronic inflammation that underly malignancy development, and (2) the mechanisms restricting the disturbances of epithelial regeneration. Finally, the results of HLDF effects depend on balance between proand antioncogenic cytokines produced by immune cells.